Air pollution and diabetes-related biomarkers in non-diabetic adults: A pathway to impaired glucose metabolism?. (March 2019) - Lucht, Sarah; Hennig, Frauke; Moebus, Susanne; Führer-Sakel, Dagmar; Herder, Christian; Jöckel, Karl-Heinz; Hoffmann, Barbara; ,
Abstract: Background: While prior studies have linked air pollution (AP) to diabetes prevalence and incidence, few have investigated whether AP exposure is also associated with alterations in diabetes-related biomarkers in metabolically healthy adults. Objective: To evaluate the associations between short-, medium-, and long-term AP and diabetes-related biomarkers (adiponectin, interleukin-1 receptor antagonist [IL-1RA], high sensitivity C-reactive protein [hsCRP], fibrinogen) in persons without diabetes. Methods: Adiponectin, IL-1RA, hsCRP, and fibrinogen were measured in blood samples collected at the baseline (t0 ; 2000–2003) and first follow-up (t1 ; 2006–2008) examinations of the prospective Heinz Nixdorf Recall (HNR) cohort study in Germany. Participants' residential mean exposures to PM10, PM2.5, NO2, and accumulation mode particle number concentration (PNAM ) were estimated for several time windows (1- to 365-day) prior to examination using a dispersion and chemistry transport model. We fitted covariate-adjusted linear mixed effects models using a random participant intercept and investigated effect modification by obesity status. Results: We analyzed 6727 observations (nt0 = 3626, nt1 = 3101) from 4052 participants of the HNR study (52% women; ages 45–76 years at t0 ). For all air pollutants, medium-term exposures (60- to 120-day) were negatively associated with adiponectin (e.g., 91-day PNAM : −2.51% change [−3.40%, −1.53%] per interquartile [IQR] increase). Several short-, medium-, and long-term AP exposures were positively associated with IL-1RA (e.g., 365-day PM10 : 2.64% change [1.25%, 4.22%] per IQR increase). Long-term exposures were positively associated with hsCRP level while no consistent patterns were observed for fibrinogen. Stronger associations for adiponectin were observed among non-obese participants. Conclusion: In persons without diabetes, we observed differing patterns of association between AP and diabetes-related biomarkers across a range of exposure windows, supporting the hypothesis that AP may play a role in the development of diabetes. Highlights: Air pollution associated with diabetes-related biomarkers in non-diabetic adults Differing temporal patterns of association for each biomarker Negative association with adiponectin seen primarily in lean individuals